Novel Mutation of the TINF2 Gene in a Patient with Dyskeratosis Congenita - Benjaporn Panichareon; Thanawat Seedapan; Wanna Thongnoppakhun; Chanin Limwongse; Manop Pithukpakorn; Thawornchai Limjindaporn (Karger Publishers, 2015)
Dyskeratosis congenita (DKC) is a rare inherited disease that is characterized by abnormal skin pigmentation, nail dystrophy and mucosal leukoplakia. DKC is caused by an abnormality in a component of the telomerase and shelterin complexes. TINF2 encodes a protein in the shelterin complex and TERC encodes a component of the telomerase complex. Mutations of both genes have been associated with DKC. This study examined mutations in TINF2 and TERC by direct DNA sequencing in a Thai patient with DKC. We identified a novel mutation (c.845G>T) that is located in exon 6 of TINF2 and changes an arginine to leucine (Arg282Leu). This identified mutation could be applied for molecular genetic diagnosis and genetic counseling of patients with DKC.